Bio-Inspired Knee Joint: Trends in the Hardware Systems Development - Etoundi, Appolinaire C.; Semasinghe, Chathura L.; Agrawal, Subham; Dobner, Alexander; Jafari, Aghil (Frontiers in Robotics and AI, 2021)
The knee joint is a complex structure that plays a significant role in the human lower limb for locomotion activities in daily living. However, we are still not quite there yet where we can replicate the functions of the knee bones and the attached ligaments to a significant degree of success. This paper presents the current trend in the development of knee joints based on bio-inspiration concepts and modern bio-inspired knee joints in the research field of prostheses, power-assist suits and mobile robots. The paper also reviews the existing literature to describe major turning points during the development of hardware and control systems associated with bio-inspired knee joints. The anatomy and biomechanics of the knee joint are initially presented. Then the latest bio-inspired knee joints developed within the last 10 years are briefly reviewed based on bone structure, muscle and ligament structure and control strategies. A leg exoskeleton is then introduced for enhancing the functionality of the human lower limb that lacks muscle power. The design consideration, novelty of the design and the working principle of the proposed knee joint are summarized. Furthermore, the simulation results and experimental results are also presented and analyzed. Finally, the paper concludes with design difficulties, design considerations and future directions on bio-inspired knee joint design. The aim of this paper is to be a starting point for researchers keen on understanding the developments throughout the years in the field of bio-inspired knee joints.